(untitled) (Revista horizonte, 2014)
Objective: To analyze and compare the morphological aspects of professional and semiprofessional Chilean footballers. Sample: We have studied 44 football players, 22 from Ñublense Sports Club an and 22 from the Valdivia Sports Club, with mean age of 22.42 ± 4.20 years, mean weight of 73.25 ± 6.64 kg, and mean height of 175.31 ± 6.26 cm. Methods: To evaluate body composition, the Deborah Kerr (1988) formula is used, which is divided into 5 categories Fat Mass (MA), Muscle Mass (MM), Bone Mass (MO), Residual Mass (MR) and Skin Mass(MP) and to calculate somatotype, the Carter and Heath (1990) formula is used, determining the Endomorphic, Mesomorphic and Ectomorphic components that classify somatotype, as recommended by the International Society of Kinanthropometry (ISAK). Results: Body composition show the following average values; MA 16.54 + 3.06, MM 33.27 + 4.49, MO 9.00 + 1.17, MR 8.72 + 1.03, MP 4.00 + 0.32 and a mean somatotype of 2.3 + 0.92 Endo, 4.8 + 1.05 Meso and 2.1 + 0.90 Ecto. Its classification is Balanced Mesomorphic. Conclusions: In body composition statistically significant differences are appreciated both in muscle mass and adipose tissue between the players of Ñublense Sports Club and Valdivia Sports Club. In somatotype, differences were observed in field positions which are not statistically significant, in all position mesomorphism prevails which responds to the normal characteristics of morphic type in professional footballer in various countries, however, a reduction is detected in the percentages of lean mass (MM), and an increase of fat mass (MA), that can identify clear differences in performance relative to the positions of the field in competitive situations.